HOW STEM APPROACH THE DEVELOPMENT OF STUDENTS’ CRITICAL THINKING SKILLS IN SCIENCE EDUCATION? SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Nurmala Sari (Relativitas: Jurnal Riset Inovasi Pembelajaran Fisika, 2026)
This systematic review attempts to close the gap by thoroughly examining the body of research to determine how well the STEM approach fosters students' critical thinking abilities. This study's methodology is a Systematic Literature Review, which yielded 224 papers from 2013 to 2025 by utilizing the keyword "STEM approach critical thinking skills in science education" in the "Article Title, Abstract, and Keywords" section of the Scopus database. The evaluation was conducted on September 10, 2025. The collected data will undergo bibliometric analysis using VOSviewer. Based on an analysis of 48 Scopus publications, the STEM framework proves successful at developing critical thinking among students, but the number of studies on this topic is still limited, indicating a research gap. STEM equips students with 21st-century skills and socio-ethical sensitivity, which is strengthened by technologies such as robotics and Metaverse. Research is dominated by the US and Indonesia, with the University of Lampung as the main contributor. Theoretically, this analysis serves as a roadmap for future research. Practically, these findings encourage educators to implement STEM as a strategy to prepare students for the challenges of the modern world, while highlighting the importance of global collaboration in this field.